KEEFEKTIFAN MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENULIS TEKS EKSPOSISI SISWA KELAS X SMAN 1 BAMBAIRA KABUPATEN PASANGKAYU - Syaripuddin, Syaripuddin; Suputra, I Gusti Ketut Alit; Harisah, Sitti (BAHASANTODEA, 2017)
This research was experimental research. The formulation of the problem in this reserach amounted to three, namely (1) How is the ability to write exposition text in class X MIPA of SMAN 1 Bambaira Pasangkayu Regency?, (2) How is the implementation of exposition text writing learning with problem-based learning model at class X MIPA of SMAN 1 Bambaira Pasangkayu Regency? The results of the ability to write exposition text in the experimental class and the control at class X MIPA of SMAN 1 Bambaira Pasangkayu Regency? This research aims to test the problem-based learning model in order to improve the ability to write exposition text so that the teaching learning process model becomes an alternative learning to write exposition text. This research was a quasi-experimental research method. The design in this research was a quasi experimental design. The population of this research was all students at class X of SMAN 1 Bambaira. The samples were two classes, namely class X MIPA 1 as the experimental class and class X MIPA 2 as the control class. The structure and rules of the exposition text assessed in this research cover five aspects, namely content, text structure, vocabulary, sentence effectiveness, and mechanics. Based on the results of statistical tests, data obtained from the calculation of t-test Sig are obtained 'the ability to write exposition text is 0.035. The significance level in this research was 0.05 (95% confidence level). Based on these calculations, the results of the hypothesis Ho is rejected or the hypothesis Ha is accepted, there is a significant difference between the ability to write exposition text in the experimental class using a problem-based learning model and a control class with a learning model not using problem-based learning at class X of SMAN 1 Bambaira Pasangkayu Regency.